The Effectiveness Of The Implementation Of Experiences Framework, Language, Pictures, Symbols, And Application (ELPSA) Cooperative Setting Of Students Teams Achievemet Division (STAD) Type In Mathematics Subjects On Set Material Of Grade VII at SMPN 29 In Bulukumba - Dwinto Reskiawan (Universitas Negeri Makassar, 2020)
The research aimed at describing the Effectiveness of Experiences, Language, Picture, Symbols, and Application (ELPSA) on Cooperative Setting of Students Teams Achievement Division (STAD) Type in Mathematics Subjects on class X SMP Negeri 29 Bulukumba. The populations of this research were all students of grade class X SMP Negeri 29 Bulukumba and choose one class as the sample of the research by using simple random sampling as the experiment class, clas VII A, was given the treatment of Experiences, Language, Picture, Symbol, and Apllication (ELPSA) Cooperative Setting on STAD type. The data collections consisted of the data of learning model implementation, data of students’ activities, in learning process, data of students’ response on learning instruments, and data of students’ learning result which consisted of the pretest and posttest scores. The data of learning model implementation, students’ activities, and students’ response data were analyzed by using statistic descriptive analysis; whereas, mathematics learning result os students was analyzed by employing statistics descriptive and statistics inferential analysis. The results of the research revealed that (1) the average score of learning implementation level (TKP) was in good criteria (3.50 ≤ x ≤ 4.50) which was 3.17; (2) the average score of students’ activity had met sufficiently active criteria (2.5 – 3.4) which was 2.87; (3) students’ responds is in positive category (3.50 – 4.0) which was 3.51; (4) the everage of students’ learning result before the treatment was in very low category (0 – 54) which was 31.37 from the ideal score 100. The everage of students’ learning result after the treatment was in high category (80-89) which was 81.68 from the ideal score of 100. The everage of students’ improvement score (gain value) was in high category (x ≥ 0.7) which was 0,73. Based on inferential statistic analysis on students’ learning result after the treatment, it was obtained P-value < α (0.01 < 0.05) so H0 was rejected and H1 was accepted where the everage of students’ learning result was higher than 74.9 (KKM), and the everage of students’ learning improvement score (gain value) obtained P-value < α (0.01 < 0.05), so H0 was rejected and H1 was accepted where the everage of students improvement score (gain value) was higher than 0.29. Based on the results of the analysis of the level of holistic learning effectiveness concluded that the implementation of Experiences, Language, Picture, Symbol, and Apllication (ELPSA) on Cooperative Setting of Students Teams Achievement Division (STAD) Type is quite effective to be implemented in Mathematics subjects on class X SMP Negeri 29 Bulukumba.